2023
DOI: 10.3389/fpsyg.2023.1200614
|View full text |Cite
|
Sign up to set email alerts
|

Does mental health limit organizational behavior, or not? A study drawn on resource conservation

Abstract: The current study is rooted in the theory of conservation of resources, exploring the associations between mental health factors namely stress, anxiety and depression with organizational citizenship behavior and counterproductive wok behavior. Data gathered from an Indian automobile sector revealed interconnections between the variables. It was found that stress, anxiety and depression have a positive relationship with OCB and stress and anxiety have negative relationship with CWB. The manuscript further evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…These findings are also consistent with the negative state relief model proposed by Cialdini and Kenrick (1976) and Cialdini et al (1982) which suggested that altruistic behavior is motivated by a desire to alleviate one's own feelings of unhappiness or discontentment. Therefore, it is reasonable to assume that engaging in any type of constructive behavior (such as OCBs) can help reduce stress (Jain and Cooper, 2012;Singh and Bhuvaneswari, 2023). OCB resources increase stress reactions which establishes that even a positive behavior can give rise to stress in an individual leading to a kind of coping mechanism at work in turn leading to other mental health outcomes (Bolino and Turnley, 2005;De Clercq and Belausteguigoitia, 2020).…”
Section: Conservation Of Resources On Ocb and Cwbmentioning
confidence: 99%
“…These findings are also consistent with the negative state relief model proposed by Cialdini and Kenrick (1976) and Cialdini et al (1982) which suggested that altruistic behavior is motivated by a desire to alleviate one's own feelings of unhappiness or discontentment. Therefore, it is reasonable to assume that engaging in any type of constructive behavior (such as OCBs) can help reduce stress (Jain and Cooper, 2012;Singh and Bhuvaneswari, 2023). OCB resources increase stress reactions which establishes that even a positive behavior can give rise to stress in an individual leading to a kind of coping mechanism at work in turn leading to other mental health outcomes (Bolino and Turnley, 2005;De Clercq and Belausteguigoitia, 2020).…”
Section: Conservation Of Resources On Ocb and Cwbmentioning
confidence: 99%